Harmony in Diversity: The Role of Minority Jurisprudence in Realizing Religious Harmony in Jayapura, Papua - Moh. Wahib Aziz; Amri Amri; Ahmad Havid Jakiyudin; Siti Aminah (Justicia Islamica, 2024)
This research aims to answer how the ideal model of minority fiqh implementation in Jayapura Regency and its contribution to religious harmony in Indonesia. This research is a juridical-empirical research with normative theological and sociological approaches. The data was analysed using descriptive qualitative method. The research data was obtained through interviews and observations of informants and research locations in Jayapura. In contrast, document data was obtained from various literature sources, such as books, journal articles, and research reports. Based on the research conducted, the results show that the implementation of the fiqh of the Muslim Minority of Jayapura Regency can be formulated in 4 four models: 1) taking the opinion of the madzhab that facilitates the uncleanliness of dogs and pigs; 2) allowing Muslims to say Merry Christmas to Christians; 3) being able to participate in ceremonial activities and Christmas committees, and 4) the permissibility of electing non-Muslim leaders. Based on the research findings, it shows that there are factors driving the implementation of the fiqh of religious harmony by Muslim minority communities in Jayapura Regency. This research also contributes to realising religious moderation in a pluralistic society.